Analyzing Stock Price Volatility: A Statistical Study of Three Listed Companies on the Dhaka Stock Exchange - Shikder, Md. Jakaria Hossen; Himel, Nasiruddin Mahmud; Siddiqui, Nafisa; Rahman, M. M. (Asian Business Review, 2025)
This study focuses on the Dhaka Stock Exchange (DSE) volatility, employing GARCH (Generalized Autoregressive Conditional Heteroscedasticity) models and various statistical and mathematical methods to forecast the future volatility of selected companies. The analysis covers stock market volatility from January 2018 to June 2023, using the daily closing prices of Arab Bangladesh Bank Limited (ABBL), Bata Shoe Company (Bangladesh) Limited (BATA), and Jamuna Oil Company Limited (JOCL). The results indicate that the time series distribution of the companies’ daily returns exhibits non-stationary behavior with both positive and negative skewness. High volatility and rapid fluctuations are observed, particularly in ABBL and BATA compared to JOCL. The calculated standard deviation of BATA’s volatility highlights significant and unpredictable price movements 2022 (1.16%) and 2021 (0.73%). Finally, JOCL’s stock volatility has shown a declining trend over the past three years relative to the other two firms.